The Effectiveness of Dialectical Behavior Therapy on Self-Control and Attachment Security in Self-Injurious Adolescent Girls - Alaeinejad, Neda; Torkan, Hajar; Yousefi, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the effectiveness of dialectical behavior therapy on attachment security and self-control in self-injurious adolescent girls.Methods and Materials: This research was quasi-experimental with a pretest-posttest-follow-up design. The statistical population included all female students with self-injurious behaviors in Isfahan City, from whom 40 individuals were purposefully selected based on inclusion and exclusion criteria and were randomly assigned to the control and experimental groups. While the control group was placed on a waiting list, the experimental group received eight ninety-minute sessions of dialectical behavior therapy training. The research instruments included the Experiences in Close Relationships Questionnaire (Fraley et al., 2000) and the Self-Control Scale (Tangney et al., 2008), which were administered to participants in both groups at three stages: pretest, posttest, and follow-up. Descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures analysis of variance) were used to analyze the data.Findings: The results indicated that this method led to improvements in both variables (p < .05).Conclusion: Based on these findings, it can be concluded that this method is suitable for improving these two variables among girls with high-risk behaviors.